2022
DOI: 10.1038/s41467-022-28118-w
|View full text |Cite
|
Sign up to set email alerts
|

Hemoglobin in the blood acts as a chemosensory signal via the mouse vomeronasal system

Abstract: The vomeronasal system plays an essential role in sensing various environmental chemical cues. Here we show that mice exposed to blood and, consequently, hemoglobin results in the activation of vomeronasal sensory neurons expressing a specific vomeronasal G protein-coupled receptor, Vmn2r88, which is mediated by the interaction site, Gly17, on hemoglobin. The hemoglobin signal reaches the medial amygdala (MeA) in both male and female mice. However, it activates the dorsal part of ventromedial hypothalamus (VMH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…To investigate if VNO neurons are indeed activated by cat saliva, we analyzed immunoreactivity (IR) of phosphorylated ribosomal protein S6 subunit, pS6, in the VNO of mice exposed to cat saliva. As the cellular pS6 level is greatly upregulated upon activation of VNO neurons, it has been used as a sensitive marker to examine neural activation in the VNO (Carvalho et al, 2020; Itakura et al, 2022; Osakada et al, 2022; Tsunoda et al, 2018). We observed that exposure to both fresh and old cat saliva induced an increase in pS6-IR in the basal VNO neurons that express Gαo protein (Figure 2E, G).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To investigate if VNO neurons are indeed activated by cat saliva, we analyzed immunoreactivity (IR) of phosphorylated ribosomal protein S6 subunit, pS6, in the VNO of mice exposed to cat saliva. As the cellular pS6 level is greatly upregulated upon activation of VNO neurons, it has been used as a sensitive marker to examine neural activation in the VNO (Carvalho et al, 2020; Itakura et al, 2022; Osakada et al, 2022; Tsunoda et al, 2018). We observed that exposure to both fresh and old cat saliva induced an increase in pS6-IR in the basal VNO neurons that express Gαo protein (Figure 2E, G).…”
Section: Resultsmentioning
confidence: 99%
“…These approaches are technically challenging and may provide false positive results. Therefore, identified receptors need to be further confirmed by examining necessity and sufficiency for detecting cat saliva using genetically modified mouse lines (Haga et al, 2010;Haga-Yamanaka et al, 2014;Isogai et al, 2018;Itakura et al, 2022;Osakada et al, 2022Osakada et al, , 2018Tsunoda et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, Vmn2r114, close homolog of Vmn2r115 and Vmn2r116, is also expressed by large numbers of cells. Vmn2r88, a hemoglobin receptor 101 , was not identified as a highly expressed gene. The functions of other highly expressed receptors are not known.…”
Section: E)mentioning
confidence: 96%
“…Nevertheless, significant progress has been made in associating various pheromones with specific VRs and their resultant behavioral responses, which were further confirmed by VR knockout mouse studies. A number of studies have identified specific ligand-receptor pairs that mediate behaviors through the VNO (see Table 1) (Bufe et al, 2019;Haga et al, 2010;Isogai et al, 2018;Itakura et al, 2022;Kimoto et al, 2005;Osakada et al, 2022Osakada et al, , 2018. Moreover, several groups of chemicals and proteins have been identified to activate VSNs that express specific VRs, potentially influencing mouse behaviors.…”
mentioning
confidence: 99%